Success management in information systems projects – work-in-progress - Takagi, Nilton Hideki (2020)
In many cases, Information Systems (IS) and Information Technology (IT) projects are still underachieved, over-budget, delayed, or considered unsuccessful. One reason for this to happen is that IS project management is not trivial, even for experienced managers. In IS projects, managers and their teams need to manage several variables related to the project management knowledge areas (e.g., cost, scope, stakeholders), combine them with change management, together with many organizational variables (e.g., organizational culture) and IT-related aspects (e.g., IT adoption). Project management standards and guides (e.g., ISO 21500, PMBOK, PRINCE2), as benchmarks of good practices for structuring project management, are valuable aids in this context. However, they do not explicitly describe how success should be managed throughout a project. Aiming to contribute to fill this gap, this work-in-progress research proposes to detail the activities needed to manage success in IS projects as well as their integration into project management standards and guides, thus contributing to avoid resource waste and raise project success rates.